Social Construction of Beauty and Nonverbal Communication in Female Frontliner Recruitment - Aulia, Dinda; Alfarabi, Alfarabi; Marlina, Neneng Cucu (Journal of Social Studies Arts and Humanities (JSSAH), 2025)
This study explores the role of nonverbal communication in shaping the “good looking” criteria during the recruitment process of female frontliners at BRI Bank Bengkulu. Appearance and nonverbal cues are often perceived as indicators of professionalism and service quality in the banking sector. Using Berger and Luckmann’s social construction theory, the study analyzes how beauty standards are formed and sustained through the processes of externalization, objectification, and internalization. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with seven informants, consisting of Human Resource staff and prospective female applicants, along with documentation of company recruitment policies. The findings reveal that nonverbal communication elements—such as facial expressions, body posture, grooming, and attire play a significant role in constructing an image of professionalism and trustworthiness. However, the “good looking” standard also creates psychological pressure and perceived discrimination among candidates who do not meet visual expectations. These beauty oriented criteria, while reinforcing the corporate image, tend to overshadow technical competence and merit-based assessment. The study concludes that the overemphasis on physical appearance in recruitment reflects a socially constructed norm that perpetuates inequality and calls for a more balanced evaluation system emphasizing skill, competence, and personality.